Piecewise-polynomial approximations for the solutions of impulsive differential equations - Bilenko, V. I.; Bozhonok, K. V.; Dzyadyk, S. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
On the basis of V. Dzyadyk’s approximation method, we consider the problems of construction and theoretical substantiationof high-precision numerical-analytic algorithms for the piecewise polynomial approximation of the solutions of problemswith pulsed action.